Applications of sonodynamic therapy combined with nanobiotechnology in the treatment of digestive tract tumors - Menghan Gui; Xinmei Zheng; Hexin Fu; Mingming Cang; Haokai Ma; Jingshu He; Dong Tang (Discover Oncology)
Abstract In gastrointestinal tumor treatment, conventional therapies are often limited by challenges such as tumor heterogeneity, high invasiveness, and recurrence rat. In recent years, sonodynamic therapy (SDT) has emerged as a promising alternative, leveraging sonosensitizers and ultrasound to disrupt cancer cells through microbubble vibrations, singlet oxygen generation, and immunogenic cell death. SDT also inhibits tumor vasculature and angiogenesis, enhancing its efficacy. However, the clinical application of SDT is currently hindered by limitations, such as poor water solubility and susceptibility to hypoxic tumor environments. Nanomaterial carriers, such as zeolitic imidazolate frameworks (ZIF-8), address these issues by targeting reactive oxygen species release and activating chemotherapeutic agents like tirapazamine (TPZ), improving therapeutic outcomes and safety. This review explores the fundamental principles of SDT, its integration with nanomaterials, and future directions in gastrointestinal tumor treatment.